Solution Manual of Differential Equations - Tay , Choo Chuan; Abd. Razak, Norazlina; A. Rahman, Norasra (Penerbit Universiti, UTeM, 2008)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding.